RESTRIÇÃO FINANCEIRA E AGRESSIVIDADE TRIBUTÁRIA: UMA ANÁLISE A PARTIR DE UMA PROXY ALTERNATIVA - Souza, Wives Leal de (2020)
Taxation tends to reduce the investor's profitability, increase the prices of products and services and discourage, consequently, consumption, occurring in the dead weight of the tax. To compete in the market with lower prices and more obtaining, as compa